Ecology: a primer for Christian ethics - Rolston, Holmes, 1932-2025, author; Villanova University, publisher (Colorado State University. Libraries, 2007)
"Ecology" is, etymologically, the logic of living creatures' homes. Christian ethicists find the word related to "ecumenical," with roots in the Greek "oikos," the inhabited world. There are both problems and opportunities when Christian ethicists look toward ecological science and wonder what (use) to make of it. Success depends on coupling prescriptive values with an environmental science that is descriptively accurate and operationally competent.
Keywords: conservation; ecology; ecosystems; National Environmental Policy Act; ecological theory